Kajian Pergerakan Truk Transport TBS Sebagai Bagian Dari Rantai Pasok Bahan Pabrik Kelapa Sawit - Krisdiarto, Andre Wahyu; Wisnubhadra, Irya (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 8 No 1 (2023)DO - 10.24843/JITPA/2023.v08.i01.p03, 2023)
The transportation of oil palm fresh fruit bunches (FFB) is a crucial stage in the palm oil production system. Productivity and efficiency due to the movement of haul trucks also affect the smooth supply chain of FFB as a material for palm oil mills (PMKS). This paper presents the results of a study that aims to compare the productivity and efficiency of truck movement in the process of evacuating fruit from the yield collection point (TPH) to the PMKS, between direct and transit systems. The efficiency or level of truck utility will affect the supply of FFB for PMKS. In trucks and systems that are less efficient, the FFB supply chain for mills stagnates, which can result in reduced volume and quality of CPO output. The research method is to measure the time of each stage of the FFB evacuation, record the data on the weight of the load, measure the distance traveled, calculate the truck cycle time, productivity level, and the efficiency of the truck movement, then analyze the statistics with the T test. The results showed that there was a difference in performance between transit evacuation system with direct evacuation system to PMKS. In the transit system, truck cycle time = 3.5 hours, truck work efficiency = 44.3%, and truck productivity = 15.4 tons/day. While in direct system, the cycle time = 5.07 hours, work efficiency = 63.3%, and productivity = 12.07 tons/day. Recommendations from the research for improving the FFB supply chain are 1) doubling the supply of FFB from small transport in the transit system, 2) optimizing truck mobility by setting work locations